Brain and gonadal aromatase activity and steroid hormone levels in female and polymorphic males of the peacock blenny Salaria pavo - Gonçalves, David (2012)
In the peacock blenny Salaria pavo large males with well-developed secondary sexual characters establish nests and attract females while small “sneaker” males mimic female sexual displays in order to approach the nests of larger males and parasitically fertilize eggs. These alternative reproductive tactics are sequential, as sneakers irreversibly switch into nesting males. This transition involves major morphologic and behavioral changes and is likely to be mediated by hormones. This study focuses on the role of aromatase, an enzyme that catalyses the conversion of androgens into estrogens, in the regulation of male sexual polymorphism in S. pavo. For this, sex steroid plasma levels and aromatase activity (AA) in gonads, whole brain and brain macroareas were determined in sneakers, transitional males (i.e. sneakers undergoing the transition into nesting males), nesting males and females collected in the field. AAwas much higher in ovarian tissue than in testicular tissue and accordingly circulating estradiol levels were highest in females. This supports the view that elevated AA and estradiol levels are associated with the development of a functional ovary. Transitional males are in a non-reproductive phase and had underdeveloped testes when compared with sneakers and nesting males. Testicular AA was approximately 10 times higher in transitional males when compared with sneakers and nesting males, suggesting high AA has a suppressive effect on testicular development. Nesting males had significantly higher plasma levels of both testosterone (T) and 11-ketotestosterone when compared with the other male morphs and previous studies demonstrated that these androgens suppress female-like displays in sneakers. In the brain, AA was highest in macroareas presumably containing hypothalamic nuclei traditionally associated with the regulation of reproductive behaviors. Overall, females presented the highest levels of brain AA. In male morphs AA increased from sneakers, to transitional males, to nesting males in all brain macroareas. These results suggest that the transition into the nesting male tactic is accompanied both by an increase in testicular androgen production and by a higher conversion of androgens into estrogens in the brain. The increase in androgen production is likely to mediate the development of male secondary sexual characters while the increase in brain AA may be related to the behavioral changes associated with tactic transition.